Thermal performance of glass fiber reinforced intumescent fire retardant coating for structural applications - Faiz, A. (Microscopy Society of Malaysia, 2014)
The results of influence of glass fiber addition into the basic intumescent coating formulation towards the enhancement of its thermal insulation properties are presented. The intumescent coatings were formulated from expandable graphite, ammonium polyphosphate, melamine, boric acid, bisphenol A epoxy resin BE-188, polyamide amine H-2310 hardener and fiberglass (FG) of length 3.0 mm. Eight intumescent formulations were developed and the samples were testedfor their fire performance by burning them at 450Â°C, 650âC and 850Â°C in the furnace for two hours. The effects of each fire test at different temperatures; low and high temperature were evaluated. Scanning Electron Microscope, X-Ray Diffraction technique and Thermo Gravimetric Analysis were conducted on the samples to study the morphology, the chemical components of char and the residual weight of the coatings. The formulation, FG08 containing 7.0 wt glass fiber provided better results with enhanced thermal insulation properties of the coatings. Â© 2019, Microscopy Society of Malaysia. All rights reserved.